2011
DOI: 10.3233/jad-2011-110281
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Genome Damage and its Repair in Neurodegenerative Diseases: Function of Transition Metals as a Double-Edged Sword

Abstract: The neurons in the central nervous system (CNS) with high O2 consumption and prolonged life span are chronically exposed to high levels of reactive oxygen species (ROS). Accumulation of ROS-induced genome damage in the form of oxidized bases and single-strand breaks (SSBs) as well as their defective or reduced repair in the brain has been implicated in the etiology of various neurological disorders including Alzheimer’s/Parkinson’s diseases (AD/PD). Although inactivating mutations in some DNA repair genes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 132 publications
(182 reference statements)
0
59
0
Order By: Relevance
“…Numerous results have shown that oxidative stress plays a significant role in the pathogenesis of many neurodegenerative diseases in the brain. Therefore, noninvasive visualization of the redox status in the brain may be important for elucidating the involvement of ROS in many diseases such as brain tumors, stroke and Alzheimer's disease [9][10][11]. EPR imaging and magnetic resonance imaging (MRI) have frequently been used in noninvasive imaging studies of ROS in vivo [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous results have shown that oxidative stress plays a significant role in the pathogenesis of many neurodegenerative diseases in the brain. Therefore, noninvasive visualization of the redox status in the brain may be important for elucidating the involvement of ROS in many diseases such as brain tumors, stroke and Alzheimer's disease [9][10][11]. EPR imaging and magnetic resonance imaging (MRI) have frequently been used in noninvasive imaging studies of ROS in vivo [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the accumulation of 8-oxoG along with other oxidatively modified bases in the mammalian genome has been associated with a loss of cellular/tissue homeostasis, and is believed to contribute to various inflammatory processes and aging-related diseases (5, 6). In mammalian cells, oxidatively modified base lesions are repaired by the base-specific DNA glycosylases OGG1, endonuclease III-like protein 1 (NTH1), and Nei -like (NEIL1, NEIL2 and NEIL3) (7, 8). OGG1 and NTH1 incise the DNA strand via β-lyase activity, thereby generating 3′-phospho-α,β-unsaturated aldehyde terminus (3′dRP) and 5′-phosphate, while NEIL1,2 and 3 have βδ-lyase activity, thus generating 3′- and 5′ phosphate (3′P and 5′P) at the strand gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Such damage can arise from numerous exogenous and endogenous sources, resulting in a multitude of detrimental cellular effects, including mutations, genome rearrangements, altered gene expression, and the onset of cell death or senescence (9,49,50). As depicted in Figure 1 and extensively reviewed elsewhere (88), many proteins are involved in the BER pathway to remove the base lesions and complete repair.…”
Section: Introductionmentioning
confidence: 99%